Nitrogen determination by SEM‐EDS and elemental analysis. (23rd May 2013) - Gazulla, M.F.; Rodrigo, M.; Blasco, E.; Orduña, M.
Abstract : This paper describes a methodology for the analysis of nitrogen by scanning electron microscope with an energy dispersive X‐ray spectrometer (SEM‐EDS). The methodology was developed to have a rapid and accurate alternative method to the elemental analysis by combustion and thermoconductivity detection that does not imply the decomposition of the sample. Two methods by SEM‐EDS were established: a quantitative method trying to construct a calibration curve with reference materials and another using the standardless method provided with the instrument software, and the results were compared with those obtained by elemental analysis using two instruments that work at different temperature. An important matrix effect was found when trying to construct a calibration curve for SEM‐EDS for any kind of material, being corrected when using the standardless method because this method corrects the matrix effect. The quantification of nitrogen by SEM‐EDS is a good alternative to elemental analysis by combustion and thermoconductivity detection in those cases where the sample has a very high decomposition temperature. Copyright © 2013 John Wiley & Sons, Ltd.